A cross-cultural examination of the relationships between job attitudes and workplace deviance - Wang, Qiang; Lin, Mei Hua *; Narayan, Anupama; Burns, Gary N.; Bowling, Nathan A. (Springer, 2022)
A growing scientific literature has examined the predictors of workplace deviance, with much of this research focusing on job attitudes—particularly job satisfaction and organizational commitment—as antecedent variables. Because this research has primarily been conducted within North America, little is known about whether or not the relationships between attitudes and deviance vary across cultures. Thus, in the current research we examined the job attitude-workplace deviance relationship using data collected from workers in four different countries (i.e., China, India, Malaysia, and New Zealand) and meta-analysis. Results for the Malaysian and New Zealand samples indicated that job attitudes were negatively associated with all three measures of workplace deviance. Within the Chinese sample, job satisfaction and organizational commitment were only modestly related to three and two measures of workplace deviance, respectively. Moreover, within the Indian sample, job attitudes were not significantly related to any form of workplace deviance. Finally, the meta-analytic comparisons lent further support to the variability in the job attitude-workplace deviance relationship across cultures.